Metabolism of sugar cane plant cultivated in vitro at different nitrogen levels - Donato, Virgínia Maria Tenorio Sabino; Andrade, Arnóbio Gonçalves de; Souza, Eidy Simões de; França, José Geraldo Eugênio de (Pesquisa Agropecuaria Brasileira, 2003)
Sugar cane varieties (RB 732577, RB 83102, RB 75126, CB 45-3, Caiana and Co 997) were cultivated in vitro at basic MS nutritive media with different N levels (9.83 mM, 7.37 mM, 4.92 mM, 2.46 mM, 0.49 mM and 0.0 mM), in order to evaluate the efficiency in the assimilation process of this element. After 45 days of cultivation, the biomass and the ammonium, amino acid and soluble sugars contents were determined. Co 997 variety presented higher biomass gain and higher N quantity incorporated to free amino acid, showing higher efficiency in the assimilation process. Higher proportions of ammonium were observed on RB 83102 and RB 75126 varieties when cultivated at media without N, suggesting lower efficiency on the assimilation process due to the presence of lower values of free amino acids.